2012
DOI: 10.1016/j.physa.2011.11.058
|View full text |Cite
|
Sign up to set email alerts
|

Critical temperature studies of the anisotropic bilayer and multilayer Heisenberg ferromagnets in Pair Approximation

Abstract: The Pair Approximation method is applied to studies of the bilayer and multilayer magnetic systems with simple cubic structure. The method allows to take into account quantum effects related with non-Ising couplings. The paper adopts the anisotropic Heisenberg model for spin S = 1/2 and considers the phase transition temperatures as a function of the exchange integrals strength in line with the role of intra-and interplanar anisotropic interactions in the onset of low-dimensional magnetism. The compensation ef… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 46 publications
(76 reference statements)
1
34
0
Order By: Relevance
“…It is seen that T C is higher for z=6 (bulk system) for all J Ĵ // values and decreases gradually when J Ĵ // is increased, while the MFA predicts a linear decreasing [15]. Thus, our results are much closer to those obtained by field theory [16] or PA [17]. These results are equally in concordance with those obtained by Balcerzak et al [11] for S=1/2 and D=0.…”
Section: Numerical Results and Discussionsupporting
confidence: 92%
“…It is seen that T C is higher for z=6 (bulk system) for all J Ĵ // values and decreases gradually when J Ĵ // is increased, while the MFA predicts a linear decreasing [15]. Thus, our results are much closer to those obtained by field theory [16] or PA [17]. These results are equally in concordance with those obtained by Balcerzak et al [11] for S=1/2 and D=0.…”
Section: Numerical Results and Discussionsupporting
confidence: 92%
“…The observation by Nienhuis et al [39] is crucial for explaining the BKT-like phenomena (η eff o ≈ 1/2 and its small temperature variation with η eff o 1/2) observed in the bilayer model. The standard procedure that we follow to describe this physics is to map the TLIA model (15) onto a height model, also known as the solid-on-solid model [39,45]. By working first on the GS manifold of the zero-field TLIA, namely, by excluding configurations that contain vortices for the moment, we assign an integer-valued height variable h i to each site i of the triangular lattice.…”
Section: Discussion: Origin Of the Pseudocritical Bkt-like Behaviormentioning
confidence: 99%
“…A number of previous studies focused on magnetic properties of simple Ising bilayers formed by two ferromagnetic (FM) layers coupled by an exchange interaction of varying strength [7][8][9][10][11][12][13][14][15][16]. Such bilayers have been shown to undergo phase transitions that belong to the 2D Ising universality class and their critical temperature is controlled by the shift exponent that depends on the interlayer to intralayer coupling ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Properties of Ising bilayers consisting of two different ferromagnetic layers coupled by either ferromagnetic (FM) or antiferromagnetic (AF) exchange interactions of varying strengths have been investigated in a number of studies [7][8][9][10][11][12][13][14][15][16]. Regarding their critical behavior, it has been found that they belong to the same universality class as a two-dimensional Ising model and their critical temperature is controlled by the so call shift exponents that depends on the interlayer to intralayer interaction ratio.…”
Section: Introductionmentioning
confidence: 99%